The national-cultural features of the language of modern advertising (Comparative study) - SOBIROVNA, MUSTAQIMOVA QUNDUZ; NAJIMOVNA, ORZIYEVA LEYLO (The journal of contemporary issues in business and government, 2021)
In the contemporary world, advertising is presented to researchers multifaceted phenomenon. A number of field of sciences are engaged in its study: journalism, sociology, psychology, economics, Public Relations(PR), etc. The variety of approaches and methods of studying the phenomenon of advertising proves its versatility and at the same time the complexity of its study. Advertising as a complex socio-cultural phenomenon affecting all spheres of public life has recently increasingly found itself in the center of scientific comprehension. The question of its study is becoming important for a wide range of humanities. The national–cultural and linguistic research of advertising is acquiring significant significance at the present time. At the cultural level the modern advertising makes a great deal on the current business affairs.